MOOD REALIZED IN THE LETTER TO THE EDITOR BY NYTIMES.COM ON MARCH, 28th 2016 - Nur Shanjiwani, Putri Maharani; Widyaningrum, Agnes (Proceeding SENDI_U, 2016)
This research paper is entitled Mood realized in the letter to the editor by Nytimes.com onMarch, 28th 2016. This research is focused to identify the mood types and speech functionfrom letter to the editor rubric by Nytimes.com entitled ‘Electronic Prescription’. This researchuses descriptive qualitative method. The writers found 3 mood types namely declarativepositive, imperative and exclamative and 2 types of speech functions namely command andstatement. The declarative positive is used to give and deliver the information, then forimperative is used to persuade, to give advice, commands, etc and exclamative is used toexpress strong feelings. The speech functions command is used to ask someone to do anythingwhile statement is used to give and deliver information by strengthening what the speakerreally wants to utter the fact to the listener. In this research the dominant mood types isdeclarative positive (40%), and for speech function is statement (80%).